2008
DOI: 10.2341/07-132
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Different Restoration Techniques on the Fracture Resistance of Endodontically-treated Molars

Abstract: SUMMARYAim: This study compared the fracture resistance of endodontically-treated mandibular molars with mesio-occluso-distal (MOD) cavities restored using different restoration techniques. Methodology: Sixty sound extracted mandibular molars were randomly assigned to six groups (n=10). Group 1 did not receive any preparation.The teeth in Groups 2-6 received root canal treatment and a MOD cavity preparation. The teeth in Group 2 were kept unrestored. Group 3 was restored conventionally with amalgam. Group 4 wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
96
3
4

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(106 citation statements)
references
References 43 publications
3
96
3
4
Order By: Relevance
“…Therefore, a restoration technique that can reinforce the weakened remaining tooth structure is fundamental to reducing the possibility of fractures. Moreover, in the selected teeth, standardized MOD cavities were prepared because this clinical condition strongly reduces resistance to cuspal fractures [2,[26][27][28][29] due to the absence of mesial and distal walls, which cause a high strain on vestibular and lingual cusps [18]. Soares et al confirmed that MOD preparation and endodontic treatment accentuated the concentration of stress inside the dental structure, mainly due to the greater removal of the dental structure [30].…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Therefore, a restoration technique that can reinforce the weakened remaining tooth structure is fundamental to reducing the possibility of fractures. Moreover, in the selected teeth, standardized MOD cavities were prepared because this clinical condition strongly reduces resistance to cuspal fractures [2,[26][27][28][29] due to the absence of mesial and distal walls, which cause a high strain on vestibular and lingual cusps [18]. Soares et al confirmed that MOD preparation and endodontic treatment accentuated the concentration of stress inside the dental structure, mainly due to the greater removal of the dental structure [30].…”
Section: Discussionmentioning
confidence: 97%
“…The teeth were stored in distilled water at room temperature for at least 72 h. For the simulation of 0.3-mm-thick periodontal ligament, each root was immersed in melted wax up to the demarcation line 2 mm apical to the cement-enamel junction [18] (CEJ; checked with a digital caliper). A metal cubic mold was used to embed all the specimens in acrylic self-curing resin (StickRESIN; Stick Tech Ltd., Turku, Finland) up to 1 mm apical to the CEJ, their long axes were oriented perpendicular to the horizon using a custom-made parallelometer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…One study of CAD/CAM three-unit polymeric fixed partial dentures (FPDs) observed significantly higher fracture load results compared to glass-ceramics, as well as conventionally polymerised resins, after different aging regimens [8]. In several studies, CAD/CAM fabricated composite overlays and crowns for premolars and molars showed high fatigue resistance and were recommended for long-term reconstructions [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…87 Although the overwhelming majority of the literature supports the need for full coverage restorations of most endodontic treated teeth, and a strong association between the success of endodontic treated teeth and crowned teeth has been shown, [88][89][90] alternatives have been suggested too. These include using complex amalgam restorations, 91,92 overlays 65 or composite restorations.…”
Section: D) To Crown or Not To Crown?mentioning
confidence: 99%